Proteomic profile of vitreous in patients with tubercular uveitis. (January 2021) - Bansal, Reema; Khan, Mohd M.; Dasari, Surendra; Verma, Indu; Goodlett, David R.; Manes, Nathan P.; Nita-Lazar, Aleksandra; Sharma, Surya P.; Kumar, Aman; Singh, Nirbhai; Chakraborti, Anuradha; Gupta, Vishali; et al.
Abstract: Objective: To elucidate disease-specific host protein profile in vitreous fluid of patients with intraocular inflammation due to tubercular uveitis (TBU). Methods: Vitreous samples from 13 patients with TBU (group A), 7 with non-TBU (group B) and 9 with no uveitis (group C) were analysed by shotgun proteomics using Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS). Differentially expressed proteins (DEPs) were subjected to pathway analysis using WEB-based Gene SeT Analysis Toolkit software. Results: Compared to control groups (B + C combined), group A (TBU) displayed 32 (11 upregulated, 21 downregulated) DEPs, which revealed an upregulation of coagulation cascades, complement and classic pathways, and downregulation of metabolism of carbohydrates, gluconeogenesis, glucose metabolism and glycolysis/gluconeogenesis pathways. When compared to group B (non-TBU) alone, TBU displayed 58 DEPs (21 upregulated, 37 downregulated), with an upregulation of apoptosis, KRAS signaling, diabetes pathways, classic pathways, and downregulation of MTORC1 signaling, glycolysis/gluconeogenesis, and glucose metabolism. Conclusion: This differential protein profile provides novel insights into the molecular mechanisms of TBU and a baseline to explore vitreous biomarkers to differentiate TBU from non-TBU, warranting future studies to identify and validate them as a diagnostic tool in TBU. The enriched pathways generate interesting hypotheses and drive further research.